Technology review of thermal forming techniques for use in composite component manufacture - Land, Patrick; Crossley, Richard; Branson, David T.; Ratchev, Svetan (SAE International, 2016)
There is a growing demand for composites to be utilised in the production of large-scale components within the aerospace industry. In particular the demand to increase production rates indicates that traditional manual methods are no longer sufficient, and automated solutions must be sought. This typically leads to automated forming processes where there are a limited number of effective options. The need for forming typically arises from the inability of layup methods to produce complex geometries of structural components. This paper reviews the current state of the art in automated forming processes, their limitations and variables that affect performance in the production of large scale components. In particular the paper will focus on the application of force and heat within secondary forming processes. It will then review the effects of these variables against the structure of the required composite component and identify viability of the technology. Through this, an understanding of the key criteria involved in the forming of composite aerospace components can be utilised to better inform improved manufacturing processes and capabilities.